HOW CELEBRITY ENDORSERS AND ADVERTISING APPEAL INFLUENCE MILLENNIAL SHOPPING INTENTIONS ON SHOPEE: BRAND IMAGE AS A MEDIATOR - Patrisius Fongo; Antonio E. L. Nyoko; Ronald P. C. Fanggidae (Journal of Management Small and Medium Enterprises (SMEs), 2025)
This study investigates the influence of celebrity endorsers and advertising appeal on millennials’ purchase intention on Shopee, with brand image acting as a mediating variable. Employing a quantitative explanatory approach, data were collected through questionnaires distributed to 100 millennial Shopee users in Kupang. The study reveals that both celebrity endorsers and advertising appeal significantly enhance brand image. However, while advertising appeal directly and positively affects purchase intention, celebrity endorsers have a negative direct effect, though they exert a positive indirect effect through brand image. These findings underscore the importance of strategic alignment between celebrities and brand identity, and highlight the crucial role of emotionally resonant advertising in driving millennial purchase behavior. The research contributes to marketing literature by integrating celebrity credibility, advertisement appeal, and brand image in one model, offering practical insights for e-commerce branding strategies targeting the millennial segment. Keywords: Celebrity Endorser; Advertising Appeal; Brand Image’ Purchase Intention; Millennials; Shopee; E-Commerce Marketing